THE STUDENTS’ CRITICAL THINKING SKILLS ON SCIENCE LEARNING SUBJECT AT 5TH GRADE IN INQUIRY LEARNING - Jupriyanto Jupriyanto; Yunita Sari (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract: This study are aims to determine the differences in students' critical thinking skills using inquiry learning model. The methods that used in this research is experimental design with Nonequivalent Control Group Design (pre-test and post test in experimental group and control group). The samples are taken using simple random sampling technique with 5th grade of A class (30) and B class (31). This study using test and documentation as the data collection techniques which will be processed to answer the specified hypothesis. The technique of data analysis using t-test result of critical thinking skills in experimental group and control group with level of 0,05 are a proved result of hypothesis-table ≤ ttable ≥ ttable that is -2,001 ≤ 4,096 ≥ 2,001 then Ha is accepted, means that both group are not the same. This indicates that there is a differences of students' critical thinking skills between students using inquiry models with students using conventional learning model (lectures and assignment). It can be concluded that the inquiry self-learning models can influence the students' critical thinking skills with the percentage score of the critical thinking skills are 55% in the experimental group and the control group are 27%. Based on the results of these research, the suggestions that researchers can convey that inquiry learning models can be used as an alternative in science learning. Keywords: Inquiry Learning Model, Critical Thinking Skill